Induced Abortion and Sub-Sequent Prevalence of Contraceptive Type - Sultana, Rabia; Khuwaja, Asifa Abdul Jabbar; Ali, Sana Mubarak (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To determine the frequency of type of contraceptive usage after counselling in women seeking post abortion care. METHODOLOGY: A quasi experimental trial was conducted at Department of Gynaecology & Obstetrics Unit-I, JPMC, Karachi from August 2014 to May 2015. A sample of 753 married women age between 18-40, who had presented for induced abortion were included in the study RESULTS: The mean ± SD age was 31.47±5.54 years which ranged from 18-40 years. After counselling, 59.1% females were started using any method of contraception. Most common method was oral contraceptive pills 27.6%, 14.6% used condoms, 11.4% had intrauterine device while 2.9% used injectable contraceptives, 1.5% used sub dermal implant & 1.1% used tubal ligation. CONCLUSION: The current study found that if females have adequate knowledge about different methods of contraception and their capability to control birth spacing. So females can adopt any methods instead of conceiving unwanted pregnancy and then to go for induced abortion.